JOB BURNOUT AND GENDER AS INDICES OF MARITAL SATISFACTION AMONG UNIVERSITY LECTURERS IN SOUTH-EAST NIGERIA - Uwaoma, Nkwam C; dney-Agbor, Ngozi N; Iroegbu, Manasseh N; Madukwe, Ann U; Njoku, Juliana (Social Science Research, 2019)
Job burnout and gender as indices of lecturers’ marital satisfaction were examined among two hundred and two lecturers (99 women and 103 men) selected via convenience sampling technique. They were drawn from three higher institutions in South-Eastern Nigeria, all within the age range of 32 and 52 years with a mean age of 43.50 years and standard deviation of 3.53. Two instruments: Maslach Burnout Inventory (MBI) and Index of Marital Satisfaction (IMS) were employed to collect data. Cross-sectional design was adopted while data were analyzed using Pearson r and t-test statistics. The results of the study showed a weak correlation between burnout and marital satisfaction and no gender differences in marital satisfaction. The findings were discussed according to relevant and available literature. The researchers recommend that lecturers should be enlightened on the early signs of burnout and to strive to protect their marital satisfaction.